2008
DOI: 10.1007/s10578-007-0092-3
|View full text |Cite
|
Sign up to set email alerts
|

The Trichotillomania Scale for Children: Development and Validation

Abstract: Trichotillomania (TTM) is a chronic impulse control disorder characterized by repetitive hair-pulling resulting in alopecia. Although this condition is frequently observed in children and adolescents, research on pediatric TTM has been hampered by the absence of validated measures. The aim of the present study was to develop and test a new self-report measure of pediatric TTM, the Trichotillomania Scale for Children (TSC), a measure that can be completed by children and/or their parents. One hundred thirteen c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 32 publications
0
40
0
Order By: Relevance
“…[16] Participants in this subgroup satisfied the following criteria: (1) both parent and child reported child hair pulling, resulting in noticeable hair loss; (2) child reported he/she ''never/almost never'' (0-10% of the time) pulled hair because voices (like an imaginary friend) told them to do so and ''never/almost never'' (0-10% of the time) pulled because they believed small bugs were crawling on them; (3) the parent reported that they did not always pull as the result of physical causes (e.g., skin conditions, physical illness, or injury) or the use of medications, drugs, or alcohol; and (4) either the parent or the child reported that the hair pulling resulted in at least ''mild to moderate'' impairment (a score of 3 or greater on a 9-point Likert-type scale) in routine social, role, or academic functioning. The DSM-IV-TR requirement of some minimal level of tension before pulling (Criterion B) that is relieved contingent on a pulling episode (Criterion C) was not required for diagnosis in the present sample or other research from our group, [12] given research suggesting that children and adolescents are less likely to endorse antecedents and consequences of pulling as compared to adults with TTM. [7,9] Child demographics.…”
Section: Participantsmentioning
confidence: 77%
See 4 more Smart Citations
“…[16] Participants in this subgroup satisfied the following criteria: (1) both parent and child reported child hair pulling, resulting in noticeable hair loss; (2) child reported he/she ''never/almost never'' (0-10% of the time) pulled hair because voices (like an imaginary friend) told them to do so and ''never/almost never'' (0-10% of the time) pulled because they believed small bugs were crawling on them; (3) the parent reported that they did not always pull as the result of physical causes (e.g., skin conditions, physical illness, or injury) or the use of medications, drugs, or alcohol; and (4) either the parent or the child reported that the hair pulling resulted in at least ''mild to moderate'' impairment (a score of 3 or greater on a 9-point Likert-type scale) in routine social, role, or academic functioning. The DSM-IV-TR requirement of some minimal level of tension before pulling (Criterion B) that is relieved contingent on a pulling episode (Criterion C) was not required for diagnosis in the present sample or other research from our group, [12] given research suggesting that children and adolescents are less likely to endorse antecedents and consequences of pulling as compared to adults with TTM. [7,9] Child demographics.…”
Section: Participantsmentioning
confidence: 77%
“…The Trichotillomania Scale for Children [12] is a 12-item self-report instrument used to assess severity and distress of hair pulling. For this study, we used the 5-item severity scale (child-reported) derived by Tolin et al [12] This scale has good internal consistency (a 5 .76) and test-retest reliability (r 5 .81); construct validity with the Clinician's Global Impression-Severity and NIMH Trichotillomania Severity Scale has also been documented.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations